Strong correlation between concentrations of tenofovir (TFV) emtricitabine (FTC) in hair and TFV diphosphate and FTC triphosphate in dried blood spots in the iPrEx open label extension: Implications for pre-exposure prophylaxis adherence monitoring - Monica Gandhi (2018)
© The Author 2015. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. Self-reported adherence to pre-exposure prophylaxis (PrEP) has limitations, raising interest in pharmacologic monitoring. Drug concentrations in hair and dried blood spots (DBS) are used to assess long-term-exposure; hair shipment/storage occurs at room temperature. The iPrEx Open Label Extension collected DBS routinely, with opt-in hair collection; concentrations were measured with liquid chromatography/tandem mass spectrometry. In 806 hair-DBS pairs, tenofovir (TFV) hair levels and TFV diphosphate (DP) in DBS were strongly correlated (Spearman coefficient r = 0.734; P < . 001), as were hair TFV/DBS emtricitabine (FTC) triphosphate (TP) (r = 0.781; P < . 001); hair FTC/DBS TFV-DP (r = 0.74; P < . 001); hair FTC/DBS FTC-TP (r = 0.587; P < . 001). Drug detectability was generally concordant by matrix. Hair TFV/FTC concentrations correlate strongly with DBS levels, which are predictive of PrEP outcomes.